2018
DOI: 10.1001/jamaoncol.2018.1621
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Validity of Nuclear-Localized Androgen Receptor Splice Variant 7 in Circulating Tumor Cells as a Predictive Biomarker for Castration-Resistant Prostate Cancer

Abstract: Importance A blood test to determine whether to treat patients with metastatic castration-resistant prostate cancer (mCRPC) with an androgen receptor signaling (ARS) inhibitor or taxane is an unmet medical need. Objective To determine whether a validated assay for androgen receptor splice variant 7 (AR-V7) protein in circulating tumor cells (CTCs) that is localized to the nucleus can predict differential overall survival (OS) in mCRPC patients treated with taxanes vs. ARS inhibitors. Design Blinded correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
193
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(216 citation statements)
references
References 31 publications
13
193
1
1
Order By: Relevance
“…The observed AR‐V7 positivity rate of 48% at baseline in this study is similar to the previously reported 18–46% (Antonarakis et al , ; Antonarakis et al , ; De Laere et al , ; Miyamoto et al , ; Scher et al , ). The lack of association between the AR‐V7 status of CTCs and outcome to taxane‐based chemotherapy confirms both our prior findings (Onstenk et al , ), as well as those of others (Antonarakis et al , ; Scher et al , ). On the contrary, an association has been reported between the presence of AR‐V7 at the protein level and worse outcome to taxane treatment, especially when the protein was localized in the cell nucleus (Scher et al , ; Scher et al , ; Tagawa et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed AR‐V7 positivity rate of 48% at baseline in this study is similar to the previously reported 18–46% (Antonarakis et al , ; Antonarakis et al , ; De Laere et al , ; Miyamoto et al , ; Scher et al , ). The lack of association between the AR‐V7 status of CTCs and outcome to taxane‐based chemotherapy confirms both our prior findings (Onstenk et al , ), as well as those of others (Antonarakis et al , ; Scher et al , ). On the contrary, an association has been reported between the presence of AR‐V7 at the protein level and worse outcome to taxane treatment, especially when the protein was localized in the cell nucleus (Scher et al , ; Scher et al , ; Tagawa et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the androgen receptor (AR) splice variant ( AR‐V ) 7 in circulating tumor cells (CTCs) was recently shown to predict resistance to new‐generation anti‐AR‐targeted treatments (abiraterone acetate and enzalutamide), but not to taxane‐based chemotherapy in patients with metastatic castration‐resistant prostate cancer (mCRPC) (Antonarakis et al , ; Antonarakis et al , ; Antonarakis et al , ; De Laere et al , ; De Laere et al , ; Nakazawa et al , ; Onstenk et al , ; Onstenk et al , ; Scher et al , ; Scher et al , ; Scher et al , ; Tagawa et al , ). If further validated, like currently ongoing in the CABA‐V7 study (NCT03050866), the AR‐V7 status of CTCs may be used in clinical care to select the best treatment for an individual patient at a specific time (Sieuwerts et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, detection of AR-V7 in CTCs, an important splice variant in the androgen receptor, is associated with resistance to hormonal therapies abiraterone acetate and enzalutamide. [16][17][18][19] Yet, despite the importance of AR-V7 as a predictive biomarker, many men with AR-V7 negative disease have resistance to therapy or develop resistance over time that is currently unexplained by AR alterations. 16,17,20 Thus, novel approaches to detect de novo biomarkers are needed.…”
Section: Inmentioning
confidence: 99%
“…6 While most men initially respond to novel hormonal therapies, such as abiraterone acetate or enzalutamide, nearly all men with mCRPC relapse and develop resistant progression over 1 to 3 years. [16][17][18][19] Yet, despite the importance of AR-V7 as a predictive biomarker, many men with AR-V7 negative disease have resistance to therapy or develop resistance over time that is currently unexplained by AR alterations. 15 Thus, optimal delivery of these agents in the second-line setting could be facilitated by the development of predictive biomarkers of treatment response and resistance.…”
mentioning
confidence: 99%
“…The paper recently published by Scher et al (8) in JAMA Oncology , reports on a multi-center validation of the EPIC Sciences AR-V7 test, an assay that requires not only immunofluorescence-based detection of the AR-V7 protein in patients’ CTCs, but also requires nuclear localization of the AR-V7 signal for a positive call. Thus, the detection of a cytoplasmic-only AR-V7 protein would not be denoted as an AR-V7(+) test by this definition.…”
mentioning
confidence: 99%